2012
DOI: 10.1080/0305215x.2012.654788
|View full text |Cite
|
Sign up to set email alerts
|

Configuration optimization of dampers for adjacent buildings under seismic excitations

Abstract: Passive coupling of adjacent structures is known to be an effective method to reduce undesirable vibrations and structural pounding effects. Past results have shown that reducing the number of dampers can considerably decrease the cost of implementation and does not significantly decrease the efficiency of the system. The main objective of this study was to find the optimal arrangement of a limited number of dampers to minimize interstorey drift. Five approaches to solving the resulting bi-level optimization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Therefore, seismically isolated structures need to be designed to perform successfully under both near-fault and far-fault types of earthquake, requiring an optimum solution. Solutions such as passive coupling of adjacent structures via optimally arranged dampers (Bigdeli, Hare, and Tesfamariam 2012) or seismic isolation systems making use of semi-active damping (Symans and Constantinou 1999;Yang and Agrawal 2002;Alhan, Gavin, and Aldemir 2006;Mehrparvar and Khoshnoudian 2012) have been proposed and are still being actively investigated by researchers; however, because of its many advantages, including but not limited to ease of implementation and design, an optimization of passive seismic isolation which presents the best performance in case of both near-fault and far-fault earthquakes may provide a preferable alternative solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, seismically isolated structures need to be designed to perform successfully under both near-fault and far-fault types of earthquake, requiring an optimum solution. Solutions such as passive coupling of adjacent structures via optimally arranged dampers (Bigdeli, Hare, and Tesfamariam 2012) or seismic isolation systems making use of semi-active damping (Symans and Constantinou 1999;Yang and Agrawal 2002;Alhan, Gavin, and Aldemir 2006;Mehrparvar and Khoshnoudian 2012) have been proposed and are still being actively investigated by researchers; however, because of its many advantages, including but not limited to ease of implementation and design, an optimization of passive seismic isolation which presents the best performance in case of both near-fault and far-fault earthquakes may provide a preferable alternative solution.…”
Section: Introductionmentioning
confidence: 99%
“…Such a result has also been confirmed by experimental testing on 2 building models of 1:4 length scale, connected by linear fluid dampers, conducted by a seismic simulator. 17 Bigdeli et al 18 have investigated 5 alternative approaches to identify the optimal arrangement of a limited number of dampers which minimize the interstory drifts, showing that increasing the number of devices does not necessarily improve the efficiency of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been reported on different damping devices, confirming the efficiency of damper connectors in mitigating the vibrations of structures [33,36,8,28,9,25,38,39,35,37,25,34,35]. The research on optimizing damper connections between adjacent buildings can be categorized into two categories: the placement of dampers; and the determination of mechanical properties for dampers [11,10]. The mechanical properties of dampers can be further subdivided into the kind of dampers used and the optimal damper coefficients required (see [10,26] or Section 3.1 herein for further details on damper coefficients).…”
Section: Introductionmentioning
confidence: 99%
“…The research on optimizing damper connections between adjacent buildings can be categorized into two categories: the placement of dampers; and the determination of mechanical properties for dampers [11,10]. The mechanical properties of dampers can be further subdivided into the kind of dampers used and the optimal damper coefficients required (see [10,26] or Section 3.1 herein for further details on damper coefficients). This paper focuses on the combined optimization of both the placement of dampers and the corresponding damper coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation